LAPAROSCOPIC CHOLECYSTECTOMY IN THE ELDERLY PATIENTS. AN EXPERIENCE AT LIAQUAT UNIVERSITY HOSPITAL JAMSHORO - Malik, Arshad M.; laghari, Abdul Aziz; Talpur, K. Altaf Hussain; Memon, Aisha; Pathan, Rafique; Memon, Jan Mohammad (Journal of Ayub Medical College Abbottabad, 2007)
Background: Advancing age with its associated co-morbidities increases the likelihood of postoperative complications as well as conversion rate during laparoscopic cholecystectomy. Recent studies have also questioned efficacy of this procedure in geriatric patients. The present study assesses the safety and applicability of laparoscopic cholecystectomy in geriatric patients. The objective of the present study was to asses safety and applicability of laparoscopic cholecystectomy in the elderly patients of 65 years and above. Methods: This is a prospective analysis of 173 patients, over 65 years of age, who underwent laparoscopic cholecystectomy from December 2002 to November 2006 at Liaquat University Hospital, Jamshoro. Patients presenting with complicated and uncomplicated gallstone disease were included in the study population and all of them were operated laparoscopically. The data included demographic details, co-morbidities, underlying biliary pathology, indications for surgery, operative and postoperative complications, morbidity and mortality, and hospital stay. The statistical analysis of the data performed on SPSS version 10. Results: Laparoscopic cholecystectomy undertaken in 173 elderly patients with a mean age of 69.72 years, out of whom 52 (30.05%) were males and 121 (69.94%) were females. Co-morbid conditions were identified in 53.17% (n=92) patients and included hypertension in 38 patients (21.96%), Diabetes Mellitus in 23 patients (13.29%), COPD in 19 (10.98%) patients, Coronary artery disease in 9 (5.20%) and cardiac arrhythmias in 3 (1.73%) patients. Indications for surgery included simple biliary colic in majority of patients (69.94%) and complicated stone disease in 52 (30.05%) subjects. There were 37 (21.38%) emergency laparoscopic cholecystectomies and 136 (78.61%) patients were operated electively. Mean operative time was 100 minutes with a SD 29.03. Fourteen (8.09 %) patients required conversion to OC (Open Cholecystectomy) due to various reasons. Mean hospital stay was 6.28 days. Overall 23 (13.29 %) patients developed postoperative complications. One patient died of acute MI on 2nd postoperative day. Conclusion: There is no undue risk in laparoscopic cholecystectomy in the elderly population and the procedure can be regarded as safe as in patients below 65 years of age. Key words: Laparoscopic cholecystectomy, Geriatric population, Morbidity.